Managerial ownership and firm value: The role of corporate social responsibility - Luluk M. Ifada; Khoirul Fuad; Lisa Kartikasari (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This study examines the effect of managerial ownership on firm value with corporate social responsibility disclosure as a mediating variable. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) and listed as LQ45 from 2017 to 2019. This study used a purposive sampling technique and 28 companies with a research period of 3 years, so that 84 samples were obtained. The data analysis techniques of this study used multiple linear regression analysis and statistical hypothesis testing with SPSS. The results show that managerial ownership has a positive effect on firm value. Furthermore, managerial ownership has a positive effect on Corporate Social Responsibility. Meanwhile, Corporate Social Responsibility has a positive effect on firm value.